A comprehensive review on the prevalence, pathogenesis and detection of Yersinia enterocolitica. Issue 70 (11th December 2019) - Shoaib, Muhammad; Shehzad, Aamir; Raza, Husnain; Niazi, Sobia; Khan, Imran Mahmood; Akhtar, Wasim; Safdar, Waseem; Wang, Zhouping
Abstract : Food safety is imperative for a healthy life, but pathogens are still posing a significant life threat. Abstract : Food safety is imperative for a healthy life, but pathogens are still posing a significant life threat. "Yersiniosis" is caused by a pathogen named Yersinia enterocolitica and is characterized by diarrheal, ileitis, and mesenteric lymphadenitis types of sicknesses. This neglected pathogen starts its pathogenic activity by colonizing inside the intestinal tract of the host upon the ingestion of contaminated food. Y. enterocolitica remains a challenge for researchers and food handlers due to its growth habits, low concentrations in samples, morphological similarities with other bacteria and lack of rapid, cost-effective, and accurate detection methods. In this review, we presented recent information about its prevalence, biology, pathogenesis, and existing cultural, immunological, and molecular detection approaches. Our ultimate goal is to provide updated knowledge regarding this pathogen for the development of quick, effective, automated, and sensitive detection methods for the systematic detection of Y. enterocolitica .